TRAINING FOR FIRE DISASTER PREPARATION AND INITIAL MANAGEMENT OF FIRE WOUND : (A STUDY AT UNIVERSITAS JENDERAL ACHMAD YANI) - Wendra Wendra; Sutrisno Sutrisno; Lukmana Lokarjana; Tezza Adriansyah Anwar; Saiful N (Journal of Business Studies and Management Review, 2020)
The fire disaster preparedness training program aims to increase knowledge and abilities regarding fire alert systems, so that it is hoped that the right attitude will be in the effort to save oneself in the event of a disaster at the campus of Universitas Jenderal Achamd Yani (UNJANI). The methods used in this program are: lectures, practice/implementation, role playing, simulation, mentoring, focus group discussions (FGD) and evaluation with the support of digital technology in the context of making disaster mitigation learning materials. The solutions are: training on fire preparedness; provision of tools, facilities and infrastructure for danger signs and instructions for evacuation and rescue in the event of a fire disaster; providing educational media for campus residents about fire alertness; burn early management training.